Sasmita Gendhingdalam Pakeliran: Dulu Dan Kini - Sri Harti (Institut Seni Indonesia Surakarta, 2019)
Sasmita gendhing is a series of words that refer to the name of the gendhing as the accompaniment of Wayang Kulit Purwa. When the wayang kulit performance refers to the overnight performance of the palace pakeliran genre, sasmita gendhing becomes a bridge between the puppeteer and the pengrawit to sound the gendhing to support certain scenes. In its development, the existence of the sasmita gendhing slowly declined, even most of the puppeteers no longer used the sasmita gendhing. The text-context approach from Heddy Shri Ahimsa is used to reveal the variety of sasmita gendhings and to find the causes for the decline in the use of sasmita gendhing. The result of the study shows the various forms of sasmita gendhing including figurative words, wangsalan, and cangkriman. Meanwhile, the cause of the decline in the use of sasmita gendhing is suspected to be due to the change of image, the free structure of the scenes, the free choice of lakon, and cross style of pakeliran.